(untitled) - World Bank (WB); Vietnam Development Report 2011 (Ha Noi, 2010)
The Vietnam Development Report is the result of a consultative process involving not only development partners but also nongovernmental organizations, academics, researchers, and independent consultants. The process has been coordinated by the World Bank. This report is organized to address the lead themes of efficiency, environmental sustainability, and equity in sectoral chapters on land, water, forests, marine resources, and mineral resources. The first chapter provides a broad overview connecting the sectoral chapters. A statistical annex provides further data in support of the text.
Keywords: Natural resources,Resource-based communities,Nguồn tài nguyên thiên nhiên; Management,Quản lý; Vietnam